27th IEEE International Conference on Distributed Computing Systems. (Computer (00189162), 2007)
The article provides information about the "27th Institute of Electrical and Electronics Engineer (IEEE) International Conference on Distributed Computing Systems." The conference which will cover several topics in distributed computing will be held on June 25-29, 2007. It will provide a forum for scientists and engineers to exhibit and discuss their respective findings concerning distributed and parallel computing.